Corporate income tax competition in the Caribbean - Nassar, Koffie (IMF [Washington]US, 2008)
Calculates average effective tax rates to measure the impact of corporate income tax competition, including the widespread use of tax holidays, in the tax base for 15 countries in the Caribbean.